Waktu Respons Transmisi Data Dalam Impelentasi Algoritma A-Star Pada Sistem Pengambilan Tempat Sampah IoT Berbasis Telegram - Sabuna, Sasridarti Tari Sejahtera; Marisa Midyanti, Dwi; Kasliono, Kasliono (Universitas Muhammadiyah Riau, 2025)
Effective waste management requires an efficient monitoring system and collection route determination. One of the main challenges is the delay in delivering information that is not yet integrated into an automated schedule. To address this, this research designs an IoT-based waste bin monitoring and collection route determination system using the A-Star algorithm, as this algorithm can efficiently determine routes by considering the distance between nodes as well as the waste volume conditions. The system is equipped with a website that displays the waste volume conditions at each node, with the resulting routes sent to officers via the Telegram platform. The focus of this research is to analyze the system's performance, specifically the data transmission response time, which is defined as the time span starting from when the sensor detects the waste volume, data is sent by the ESP32 to the server, the server processes the algorithm, until the route information or notification is received by the user. The results show that the average processing time of the A-Star algorithm on the server is 0.0135 s, the average data transmission delay is 1.2659 s or 1265.9 ms, which is categorized as POOR based on the TIPHON standard, and the average system update time is 6.38473 s.